2015
DOI: 10.1080/21645515.2015.1032489
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of measles, mumps and rubella among young adults, after 20 years of universal 2-dose MMR vaccination in Israel

Abstract: Evidence-based vaccination policy is important for the global and local efforts of achieving control over measles. In 2007, the first Israeli birth cohort to be twice vaccinated during childhood with Measles-Mumps-Rubella vaccine reached adulthood. In parallel, Israel experienced its largest measles outbreak since 1994. We aimed to assess the seroprevalence of measles IgG antibodies and concordance with rubella and mumps seroprevalence among young Israeli adults born 1988-9 in comparison to previous birth coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…Comparing to children aged 6–9 years in this study, adolescents and young adults group had OR of 0.31 and adults group had increased OR of 1.74 to have positive measles antibodies. Similar findings were elicited in a study conducted in Catalonia, Spain [8] and Israel [15]. However, the prevalence rate for measles antibodies in those studies among adolescents and young adults were higher (83.8% and 85.7% respectively) than that found in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Comparing to children aged 6–9 years in this study, adolescents and young adults group had OR of 0.31 and adults group had increased OR of 1.74 to have positive measles antibodies. Similar findings were elicited in a study conducted in Catalonia, Spain [8] and Israel [15]. However, the prevalence rate for measles antibodies in those studies among adolescents and young adults were higher (83.8% and 85.7% respectively) than that found in this study.…”
Section: Discussionsupporting
confidence: 90%
“…This result was in line with seroprevalence surveys conducted by Levine et al [15], Sultana et al [19], Yekta et al [20], Davidkin et al [21] and Onoja & Adeniji [22] but differ from a study by Poethko-Muller & Mankertz [23] which found boys had higher levels of susceptibility than girls. Aaby et al [24] also found that there were sex differences in measles vaccine efficacy in their study.…”
Section: Discussionsupporting
confidence: 88%
“…The range and type of vaccination these patients previously received should be determined. In addition, some measles patients, described in 1987 [57] and in 2007 [58], present several features consistent with AMS. We also propose to follow the patients with confirmed AMS to identify an eventual malignancy, and which childhood infections the patients have developed.…”
Section: New Aspects Of the Researchmentioning
confidence: 83%
“…We encourage scientists to use for that purpose our cohort of cHL patients, about half of whom carry MV proteins in their tumor cells. We incite the investigation of cohorts from Israeli studies, in which the patients may have suffered from AMS [57,58] and who may develop sometimes in the future a MVrelated malignancy.…”
Section: New Aspects Of the Researchmentioning
confidence: 99%
“…Thus, the number of people who would have experienced a boost to their immunity from postvaccine exposure to the virus has also decreased. In Israel, decreased IgG levels observed in younger age cohorts were attributed to lack of circulating wild-type virus and lower vaccination coverage [99]. Those born in 1977-78 had a seroprevalence of 95.6 % compared to those born in 1988-89 who had 85.7 % seroprevalence for measles, which was shown to correlate with the seroprevalence for rubella [99].…”
Section: How To Interpret Waning Immunity In Populations With Universmentioning
confidence: 99%